2020
DOI: 10.1016/j.adhoc.2020.102240
|View full text |Cite
|
Sign up to set email alerts
|

A flexible encryption technique for the internet of things environment

Abstract: IoT promises a new era of connectivity that goes beyond laptops and smart connected devices to connected vehicles, smart homes, smart cities and connected healthcare. The huge volume of data that is collected from millions of IoT devices raises information security and privacy concerns for users. This paper presents a new scalable encryption technique, called Flexible encryption Technique (FlexenTech), to protect IoT data during storage and in transit. FlexenTech is suitable for resource constrained devices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…FlexenTech is a lightweight encryption model that is adaptable. 26 The level of protection and flexibility in balancing complexity is demonstrated. The symmetric block cipher design is a FlexenTech for resource-constrained devices including wireless sensors and IoT.…”
Section: Lightweight Encryption Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…FlexenTech is a lightweight encryption model that is adaptable. 26 The level of protection and flexibility in balancing complexity is demonstrated. The symmetric block cipher design is a FlexenTech for resource-constrained devices including wireless sensors and IoT.…”
Section: Lightweight Encryption Modelmentioning
confidence: 99%
“…The condition hde 1 (k, a) and k > a is satisfied. By applying Equation (26), perform the permutation round in every encryption round.…”
Section: The Architecture Of the Lightweight Encryption Modelmentioning
confidence: 99%
“…Hence, one of our contributions of this paper is to study the evaluation of various lightweight symmetric protocols. Mainly, the AES, Speck128, Tiny Encryption Algorithm (TEA) and FlexenTech [22] with all supported key sizes (128, 192 and 256 bits) are analysed and compared. For Speck128, the 128-bit block size con guration was selected since the other block ciphers also use 128 bit blocks.…”
Section: Lightweight Encryption Algorithms Have Been Recently Proposed As a Viable Solution For Securing Wsnsmentioning
confidence: 99%
“…In addition, the authors demonstrated that the security of the cipher is largely dependent on the key length. FlexenTech [22] is another lightweight symmetric block cipher considered for resource-limited IoT and WSN devices, where primitive computations are used to encrypt a plaintext.…”
Section: Cryptographic Algorithms In Wsnsmentioning
confidence: 99%
See 1 more Smart Citation